2022
DOI: 10.1097/md.0000000000030941
|View full text |Cite
|
Sign up to set email alerts
|

The value of NSE to predict ICU mortality in patients with septic shock: A prospective observational study

Abstract: To investigate the predictive value of neuron-specific enolase (NSE) on intensive care unit (ICU) mortality in patients with septic shock. Seventy-five patients with septic shock hospitalized in the emergency intensive care unit (EICU) of Hebei General Hospital from March 2020 to September 2021 were included, and the patients’ baseline characteristics and laboratory findings were collected. NSE levels on the first and fourth days after admission were retrieved. NSE% [(NSEday1 – NSEday4)/NSEday1 × 100%] and δNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…> 12.5µg/L) in sepsis varies between 28 and 53% [ 45 , 46 ]. Previous studies showed a modest increase in NSE concentrations during sepsis, with median serum levels of 6.6 [IQR 4.1–13.8] µg/L [ 45 ], 18.8 [IQR 13.9 –30.5] µg/L [ 34 ], and 30.33 [IQR 19.6–46.5] µg/L [ 47 ].…”
Section: Blood Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…> 12.5µg/L) in sepsis varies between 28 and 53% [ 45 , 46 ]. Previous studies showed a modest increase in NSE concentrations during sepsis, with median serum levels of 6.6 [IQR 4.1–13.8] µg/L [ 45 ], 18.8 [IQR 13.9 –30.5] µg/L [ 34 ], and 30.33 [IQR 19.6–46.5] µg/L [ 47 ].…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…One prospective cohort study found no correlation between NSE levels and mortality at day 28 [ 46 ]. Conversely, two prospective cohorts found an association between NSE levels and ICU or hospital mortality (NSE at day 4 > 25.94µg/L, AUC 0.75 [ 47 ]; NSE > 24.15µg/L, AUC 0.59 [ 48 ]). Another retrospective study demonstrated that abnormal NSE levels on ICU admission were associated with a 23.3% risk of death, and each doubling of NSE level was linked to a 7.3% increased risk of death [ 45 ].…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…NSE is already utilized as a biomarker in the differential diagnosis of SCLC. Additionally, NSE holds particular prognostic value for predicting outcomes in patients with severe craniocerebral trauma [ 18 ]. NSE is a well-established marker, and its serum levels are utilized to support the initial diagnosis of SCLC.…”
Section: Introductionmentioning
confidence: 99%